EFFECTIVENESS OF ADHESIVES ON WOOD HULL LAMINATION - Dian Dolani Simanjuntak; Syaifuddin Syaifuddin; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe research aims to determine the volume of adhesive needed in laminating wooden ships to produce the maximum strength of the ship structure with the adhesive used c'ketz reinforce bond. The method used in this study is an experimental method by testing directly in a laboratory with 4 levels, namely the dose of 0 ml (without treatment), 100 ml, 150 ml, 200 ml per wood laminate with as many as 5 repetitions at each level. Data analysis used analysis of variance (Analysis of Variance) with a completely randomized design mathematical model. From the results of the study that the modulus of elasticity (MOE) of the treatment of 0 ml (control), 100 ml, 150 ml, and 200 ml respectively was 32597.36 kg/cm2, 35401.03 kg/cm2, 40939.67 kg/cm2, and 46768.81 kg/cm2 and the laminated Modulus of Repture treatment of 0 ml, 100 ml, 150 ml and 200 ml respectively with 648.5823 kg/cm2, 666.5167 kg/cm2, 731.8859 kg/cm2 and 770.6981 kg/cm2. So that the adhesive volume needed in the lamination of wooden ships to produce the maximum structural strength of the ship is the adhesive volume of 200 ml and to determine the adhesive requirements needed for laminate of the hull on the immersed part in the water it can be calculated using the formula: Adhesive Requirement (l) = 3,333 x , where x is a large WSA. Keywords: ship, adhesive, reinforce bond, Modulus of Elasticity, Modulus of